From Financial Access to Capability Expansion: A Structured Systematic Literature Review on Women, Microfinance, and Poverty Reduction - Adzan Noor Bakri; Fahira herawati; aziza samsir (LP2M IAIN Palopo, 2026)
Microfinance has long been promoted as a pathway to women’s empowerment and poverty reduction, yet the empirical literature remains fragmented across financial access, empowerment outcomes, and welfare effects. Much of the existing evidence documents changes in income, savings, household decision-making, and livelihood conditions, but fewer studies explain how access to financial resources is translated into substantive freedoms and valued ways of living. This study aims to synthesize empirical research on women, microfinance, and poverty reduction through the lens of Amartya Sen’s Capability Approach. Using a structured systematic literature review, this article reviews peer-reviewed empirical studies on women’s participation in microfinance, self-help groups, and related community-based financial mechanisms. The findings indicate that microfinance is associated with positive changes in income stability, household welfare, mobility, access to public services, social participation, and decision-making. However, these outcomes are neither automatic nor uniform. Their realization depends on a range of conversion factors, including household power relations, socio-cultural norms, institutional design, training opportunities, and infrastructural conditions. The review further shows that while the literature is rich in empowerment indicators, it remains relatively weak in explicitly capability-based analysis. This article contributes a capability-oriented synthesis that explains not only whether microfinance matters for women’s poverty reduction, but also how financial access is converted into capabilities, valued functionings, and uneven development outcomes. The study implies that microfinance policies should be assessed beyond outreach and repayment rates, with greater attention to capability expansion and the enabling conditions that allow women to transform financial access into meaningful well-being.